Spontaneous Resolution of Traumatic Macular Hole in a Child - Lalit Verma; Arindam Chakravarti; Avnindra Gupta; Smriti Prakash (Delhi Journal of Ophthalmology)
There are several published reports on spontaneous closure of idiopathic macular hole but information regarding spontaneous closure of traumatic macular hole is limited. We present a case of spontaneous resolution of post traumatic macular hole in a 9 year old child with associated visual recovery. The child was followed up for seven months and the morphological changes were documented on optical coherence tomography. The case study illustrates the role of conservative management of traumatic macular hole in selected young patients, thus preventing the need for surgical intervention and its possible difficulties and complications.